Matija Murko in predfrancoski začetki slovenske primerjalne književnosti v 19. stoletju - Smolej, Tone (Primerjalna književnost, 2025)
This article examines the comparative research done by Matija Murko during his stay in Vienna (1889–1902). His studies of The Seven Sages of Rome, encouraged by Alexander Nikolayevich Veselovsky, may be said to border on thematology. To cite an example, Murko links the narrative “Vidua” (“The Widow”) to “The Matron of Ephesus” and examines this theme both in Rus-sian folk narratives and in Polish literature. Part of his research was publis-hed in Koch’s Zeitschrift für vergleichende Litteraturgeschichte, at the time the only comparative literature periodical in the world. Three years before the renowned comparative literature congress in Paris, which established in 1900 the mutual influences of European literatures as a research topic, thus impac-ting the development of the French school, Murko published the monograph Deutsche Einflüsse auf die Anfänge der böhmischen Romantik (German Influences on the Beginnings of Czech Romanticism). Rather than engage in a detailed comparison of literary works, however, his monograph traces the concept of influence to the personal contacts established between the representatives of Czech and German literatures. Murko’s Vienna treatises may thus be perce-ived largely as the pre-French beginnings of Slovenian comparative literature.
Keywords: comparative literature; literary influences; Murko, Matija; Primerjalna književnost; Slovenian literary historians; slovenski literarni zgodovinarji; Vplivi (literarni, umetnostni itd.)